CINEMATIC DESCRIPTION THE LOCOMOTION PERFORMED IN DEEP WATER: A CASE STUDY (Fiep Bulletin - online, 2013)
This study aimed at characterizing the kinematics locomotion held in suspension in the liquid medium. This case study was to sample a man of 45 years. The angles of the joints were examined knee, hip, elbow, shoulder (for angles) and inclination of the trunk. The angular variations were measured during 03 cycles of locomotion, by shooting two-dimensional. Data analysis was used Pearson's linear correlation (p
Keywords: Locomotion; Suspension; Deepwater